(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
The implementation of the Goods and Services Tax (GST) in India represented a substantial alteration in the nation’s indirect tax framework, with the objectives of optimizing taxation, eliminating cascading effects, and establishing a cohesive national market. Small and Medium Enterprises (SMEs), integral to the Indian economy, have encountered both prospects and obstacles under this new environment. This research study examines the diverse effects of GST on SMEs, concentrating on operational efficiency, compliance obligations, cost frameworks, and market competitiveness. Primary and secondary data sources are employed to evaluate the impact of GST on company processes, cash flow management, and supply chain integration within the SME sector. The analysis indicates that although GST has improved transparency, broadened market access, and streamlined inter-state trade, it has concurrently heightened the compliance burden, necessitated technological deployment, and intensified working capital pressures on smaller firms. Policy implications and ideas are presented to tackle these difficulties and utilize GST for sustainable expansion of SMEs.